2017
DOI: 10.1002/asi.23921
|View full text |Cite
|
Sign up to set email alerts
|

Metric assessments of books as families of works

Abstract: We describe the intellectual and physical properties of books as manifestations, expressions, and works and assess the current indexing and metadata structure of monographs in the Book Citation Index (BKCI). Our focus is on the interrelationship of these properties in light of the Functional Requirements for Bibliographic Records (FRBR). Data pertaining to monographs were collected from the Danish PURE repository system as well as the BKCI (2005BKCI ( -2015 via their International Standard Book Numbers (ISBNs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 22 publications
0
23
0
Order By: Relevance
“…Second, studies of book citations have shown that they do indeed differ from citations of other types of publications in a variety of ways (Glänzel et al, 2016;Kousha et al, 2011;Leydesdorff & Felt, 2012;Torres-Salinas et al, 2014). There are also problems in bibliometrically identifying books that do not occur so much with journal papers (Giménez-Toledo et al, 2016;Williams et al, 2018;Zuccala et al, 2018;Zuccala & Cornacchia, 2016) which will be discussed in the data collection section.…”
Section: The Hybrid Methods 21 Defining the Comparator Setmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, studies of book citations have shown that they do indeed differ from citations of other types of publications in a variety of ways (Glänzel et al, 2016;Kousha et al, 2011;Leydesdorff & Felt, 2012;Torres-Salinas et al, 2014). There are also problems in bibliometrically identifying books that do not occur so much with journal papers (Giménez-Toledo et al, 2016;Williams et al, 2018;Zuccala et al, 2018;Zuccala & Cornacchia, 2016) which will be discussed in the data collection section.…”
Section: The Hybrid Methods 21 Defining the Comparator Setmentioning
confidence: 99%
“…It is necessary to investigate each one and if they do appear to refer to the same book, the citations are amalgamated. c) With entries not classified as "books" the situation is more complex (Zuccala et al, 2018;Zuccala & Cornacchia, 2016). The general possibilities are "citation", "pdf", "html" or most commonly just "blank".…”
Section: Research Papermentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, assessing books is not an easy task as there are various challenges not present in journal assessing. These unique issues are related to various 'matching' problems related to the ISBN (Zuccala & Cornacchia, 2016), insufficient indexing books in the databases (Torres-Salinas et al, 2013), a lack of widely recognized rankings of academic book publishers (Giménez , and problems with combing data on various book editions and translations into groups of works or book families (Zuccala, Breum, Bruun, & Wunsch, 2018). Thus, book evaluation is mostly based on publisher profiles (Manana-Rodriguez & Giménez-Toledo, 2018), library holdings (Biagetti, Iacono, & Trombone, 2018), internationalization indicators , book reviews (Basili & Lanzillo, 2018) and formal criteria (Kulczycki, 2018).…”
Section: Book Evaluation In European Performance-based Research Fundimentioning
confidence: 99%
“…The evaluation of scholarly books and the evaluation of journal articles each have unique issues. In terms of scholarly book evaluation, the main challenges are integrating data for a metric assessment (Zuccala and Cornacchia, 2016), combining data on books as groups of work (Zuccala et al , 2018), constructing the lists and rankings of academic publishers (Giménez-Toledo et al , 2016) and developing commercial book citation indexes (i.e. the Book Citation Index) so that it is a viable tool for carrying out international studies concerning books (Torres-Salinas et al , 2013, 2014).…”
Section: Introductionmentioning
confidence: 99%